Evolution of lateral V-defects on InGaN/GaN on Si(111) during PAMBE: the role of strain on defect kinetics. Issue 29 (4th July 2018) - Bag, Ankush; Das, Subhashis; Kumar, Rahul; Biswas, Dhrubes
Abstract : In this article, a unique correlation has been established between the defect kinetics of III-nitride adatoms and strain during plasma assisted molecular beam epitaxial (PAMBE) growth of InGaN/GaN heterostructures on silicon(111) for the first time. Abstract : In this article, a unique correlation has been established between the defect kinetics of III-nitride adatoms and strain during plasma assisted molecular beam epitaxial (PAMBE) growth of InGaN/GaN heterostructures on silicon(111) for the first time. This association identifies the possible causes for the evolution of V-defects in nitrides. While cross-sectional observations using transmission electron microscopy (TEM) exhibit common vertical V-defects, a planar view of the heterostructures reveals novel lateral V-defects under a field emission scanning electron microscope (FESEM). Additionally, the density and size of both types of V-defects were found to become altered dramatically above the critical thickness of the InGaN. Asymmetric (105) reciprocal space mapping (RSM) is used to represent the gradual minimization of strain with the increase of InGaN thickness. The autocorrelation length, as obtained by power spectral density (PSD) analysis of atomic force microscopy (AFM) topography, quantifies coalescence of the pits and defects with the relaxation of InGaN on GaN. It is proposed that primary non-threading dislocation (TD) terminated mobile hexagonal pits with varying depth coalesced to form the lateral V-defects. The vertexes of these lateral V-defects on the surface are likely to be connected to TD emanating from the buried GaN. Strain relaxation also accounts for anisotropy in lateral InGaN growth, which consequently leads to alloy inhomogeneity of InGaN as detailed by energy dispersion spectroscopy (EDS). The defects may be used to texture the InGaN surface in situ for photonic applications.